1991
DOI: 10.1002/macp.1991.021920101
|View full text |Cite
|
Sign up to set email alerts
|

Ring‐opening metathesis polymerization of norbornenes with organosilicon substituents. Gas permeability of polymers obtained

Abstract: Polymers of norbornenes with %Me3 and Si(Me2)CH,SiMe3 groups were synthesized and mass transfer properties of the polymers were studied. Ring-opening polymerizations of these monomers were realized in the presence of homogeneous WC16-based and heterogeneous Re,O,-based metathesis catalysts. Introduction of silicon-containing groups in the polynorbornene main chain results in a drastic increase of the permeability (P) and diffusion (0) coefficients for different biatomic and multiatomic gases. Comparison of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…Copolymers at all compositions gave only one T g and these values are in between the T g values of the two homopolymers. Thus, adamantane containing norbornene resulted in a polymer with a dramatically much higher T g compared to unsubstituted norbornene (271 vs. 38 (3130) °C). The T g values of the copolymers increased linearly with increasing incorporation of 3a and 3b .…”
Section: Resultsmentioning
confidence: 95%
“…Copolymers at all compositions gave only one T g and these values are in between the T g values of the two homopolymers. Thus, adamantane containing norbornene resulted in a polymer with a dramatically much higher T g compared to unsubstituted norbornene (271 vs. 38 (3130) °C). The T g values of the copolymers increased linearly with increasing incorporation of 3a and 3b .…”
Section: Resultsmentioning
confidence: 95%
“…Finally, the most promising results were achieved upon combination of these two approaches in the design and synthesis of new polynorbornenes for membrane gas separation. The first examples of the effect of introduction of siliconcontaining groups on the gas permeability of polynorbornenes were described in references [81][82] (Figs. 2, 3).…”
Section: Approaches To the Production Of Highly Gas Permeable Siliconmentioning
confidence: 99%
“…PNBs with functional groups usually are obtained via ROMP of the corresponding norbornene derivatives [15][16][17][18][19][20][21]. However, it has been reported that some functional groups such as hydroxyl and carboxylic groups would decrease the reactivity of the catalysts used for ROMP [22].…”
Section: Introductionmentioning
confidence: 99%